The Future of Higher Education: A Call for Radical Pedagogical Innovation in Post-Pandemic Times - Oben, Awu Isaac; Hui, Xu (Journal of Teaching and Learning, 2025)
The COVID-19 pandemic disrupted higher education globally, revealing both traditional pedagogies' strengths and weaknesses. As institutions turned to online learning, significant gaps in accessibility, digital literacy, and adaptability became apparent. This paper argues for a radical transformation of pedagogical innovation in post-pandemic higher education, advocating for a shift towards more flexible, inclusive, and student-centred learning models to bring the sustainable change we all want. It highlights key strategies, such as hybrid models, personalized learning, active and experiential learning, and rethinking assessment methods. These innovations, supported by digital tools, can better address diverse student needs and prepare learners for a rapidly evolving workforce. Nevertheless, institutional resistance to change, addressing the digital divide, and ensuring scalability remain potential barriers and challenges that must be overcome to achieve it. This paper, therefore, calls for collective and coordinated efforts by higher education institutions, stakeholders and policymakers to drive the required systemic change in higher education. By embracing these innovations, universities can build a more flexible, resilient, equitable, and future-ready education system that moves beyond the limitations of traditional pedagogies. The pandemic offers a unique opportunity to rethink the foundations of higher education and prioritize pedagogical practices that promote critical thinking, adaptability, and lifelong learning in an uncertain world.